THE EFFECT OF EDUCATION WITH ANIMATED VIDEOS ON KNOWLEDGE ABOUT PREVENTION OF SORE NIPPLES IN POSTPARTUM MOTHERS AT INDEPENDENT MIDWIFE PRACTICE OF SUSIANIBANYUWANGI 2025 - Endah Kusuma Wardani; Nur Alifia Umah; Wahyu Adri Wirawati (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Blistered nipples are a common problem faced by breastfeeding mothers, characterized by cracked, red, and sometimes bleeding nipples. This study aims to analyze the influence of education with animated videos on knowledge about the prevention of nipple abrasions in postpartum mothers. Method: This study used quasi-experimental pre-test and post-test design with control group. The subjects of the study of 60 postpartum mothers were divided into two groups each consisting of 30 mothers in the intervention group and 30 mothers in the control group selected by consecutive sampling. The tool used is a questionnaire. The duration of the animation video is seven days, with three sessions. The results of the analysis of the data normality test using Shapiro-Wilk with a value of ≥0.05 showed that the data was distributed normally. Data analysis using the T test is not paired with SPSS 25 for Windows. Result: Before starting the help for the intervention group showed they had an average score of 70.3. Meanwhile, the control group had an average score of 68.2. The average outcome of knowledge after intervention was given in the intervention group was 96.8 and in the control group 69.7. The results of statistical tests using unpaired T tests showed Asymp. Sig (2-tailed) ≤0.000, which indicates a significant effect of this therapy, there was a noticeable difference in how much the two groups knew about preventing sick nipples. Conclusion: Animated videos can be an alternative to increase postpartum mothers' knowledge about the prevention of putting blisters.